Kajian Tentang Uji Asumsi Klasik Berbantuan SPSS - Hutagaol, Kartini (LPPM Universitas Advent Indonesia, 2025)
The purpose of this article is to provide examples of the correct steps in using statistical tools in non-exact research. The use of statistical models should be appropriate to the problem being studied and the research needs. If statistical tools are not tailored to the research needs, the research results will be less reliable and will jeopardize the accuracy and validity of data interpretation. In reality, errors still occur in the use of statistical analysis tools. Therefore, this article can be useful as an example to assist students in writing their theses, specifically regarding the use of classical assumption test models. It is hoped that errors can be corrected to ensure the accuracy and validity of data interpretation are in line with the assumptions of the research problem.